Analisis dan Evaluasi Kebijakan Daerah Dalam Penerapan Sistem Pembelajaran Siswa Era Pandemi Covid-19 - Katili, Andi Abee Zoelthan; Katili, Andi Yusuf (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This study aims to analyze and evaluate regional policies in implementing the student learning system in the era of the covid-19 pandemic at SDN 27 Gorontalo City. This type of research uses a descriptive method with a qualitative approach. The use of this method is carried out with the researcher's consideration that the variable to be studied is single, namely describing regional policies in the application of the student learning system in the era of the covid-19 pandemic. Data collection techniques were carried out through observation, interviews and documentation to a number of predetermined informants. In addition, researchers recorded secondary data in the form of library research. The results of the research and discussion show that the learning system implemented by the local government, especially at SDN 27, has not been fully successful. This is because students lose their identity in learning because the tasks given by the teacher are mostly done by parents. Students when following the online learning system (online) or online do not focus on what their teacher is saying. Parents are forced to participate in the online learning process, this causes students to concentrate on learning between listening to the explanations of the teacher and their parents. Teachers are not optimal in carrying out the online learning process because they cannot see student activity, where students often prefer to listen to rather than pay attention to the teaching teacher who is monitored in the video.